2020
DOI: 10.1186/s13028-020-0504-y
|View full text |Cite
|
Sign up to set email alerts
|

Motile aeromonads from farmed and wild freshwater fish in northern Italy: an evaluation of antimicrobial activity and multidrug resistance during 2013 and 2016

Abstract: Background: Antimicrobial resistant bacteria are emerging biological contaminants of the environment. In aquatic ecosystems, they originate mainly from hospitals, livestock manure and private households sewage water, which could contain antimicrobial agents and resistant microorganisms. Aeromonas spp. occur ubiquitously in aquatic environments and they cause disease in fish. Motile aeromonads are also associated with human gastrointestinal and wound infections and fish can act as a transmission route of antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
5
32
0
1
Order By: Relevance
“…Aerom onas hydrophila strains are commonly resistant to ampicillin, tetracycline, and streptomycin. A 100% resistance rate to ampicillin in all A. hydrophila isolates has been reported repeatedly (Borella et al., 2020; Castro‐Escarpulli et al., 2003; Dahdouh et al., 2016; Guz & Kozinska, 2004; Radu et al., 2003; Wang & Silva, 1999; Wu et al., 2019). In addition, multidrug‐resistant strains were also detected at high rates in A. hydrophila isolates from fish and fish products.…”
Section: Microbiological Safety Of Fish and Fish Productsmentioning
confidence: 82%
See 1 more Smart Citation
“…Aerom onas hydrophila strains are commonly resistant to ampicillin, tetracycline, and streptomycin. A 100% resistance rate to ampicillin in all A. hydrophila isolates has been reported repeatedly (Borella et al., 2020; Castro‐Escarpulli et al., 2003; Dahdouh et al., 2016; Guz & Kozinska, 2004; Radu et al., 2003; Wang & Silva, 1999; Wu et al., 2019). In addition, multidrug‐resistant strains were also detected at high rates in A. hydrophila isolates from fish and fish products.…”
Section: Microbiological Safety Of Fish and Fish Productsmentioning
confidence: 82%
“…In addition, multidrug‐resistant strains were also detected at high rates in A. hydrophila isolates from fish and fish products. In particular, all A. hydrophila isolates recovered from retail fish in Malaysia (Radu et al., 2003), retail frozen fish fillets or farmed fish in Egypt (Dahdouh et al., 2016; Hafez et al., 2018), and farmed and wild freshwater fish in Italy (Borella et al., 2020) were resistant to at least three antibiotics. Multidrug‐resistant A. hydrophila against ampicillin, bacitracin, and tetracycline (tetracycline, oxytetracycline, or chlortetracycline) has also been detected in U.S. domestic catfish fillets (Wang & Silva, 1999).…”
Section: Microbiological Safety Of Fish and Fish Productsmentioning
confidence: 99%
“…To further gain knowledge on the MDR in the aquatic environmental bacteria, 25 out of 30 Aeromonas isolates showed an MDR profile to 19 antibiotics, where 83.33% of the strains were resistant to more than three antibiotic classes, indicating a high level of multi-resistance in the Tua River basin ( Figure 5). Previous studies [18,[60][61][62][63][64] reported β-lactams and quinolone-resistant isolates of Aeromonas spp. recovered from freshwater, fishes, and humans.…”
Section: Resultsmentioning
confidence: 99%
“…isolated from the Tua River, representing a potential risk to the population since an appreciable part of the population residing in the Tua River Basin still uses fish and river mussels in their daily diet. Foodborne diseases (FD) are a priority in public health issues around the world due to their incidence and mortality [64]. The genus Aeromonas is regarded not only as an important disease-causing pathogen of cold-blooded species but also as the etiologic agent responsible for a variety of infectious complications in both immunocompetent and immunocompromised persons [23].…”
Section: Resultsmentioning
confidence: 99%
“…However, the widespread use of antibiotics has led to the emergence of antimicrobial resistance in A. hydrophila and bioaccumulation in host tissues, which seriously threatened human and public health. Some strains of A. hydrophila have been found to be resistant to macrolides, tetracyclines, sulfonamides, and quinolones [ 11 , 12 ]. In response to this phenomenon, understanding of resistance mechanisms has become an urgent necessity for development of an effective therapeutic strategy against this pathogen.…”
Section: Introductionmentioning
confidence: 99%